Composite fiber, solid electrolyte comprising the same, and metal-air battery comprising the same
Patent Information
- Application Number
- CN202180015790.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-02-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-02-22
AI Technical Summary
[0044]本申请实施例的固体电解质可以包含:包含纤维素的膜;以及壳聚糖,与上述膜的上述纤维素结合。上述固体电解质能够以由上述基础复合纤维构成网络的膜形态来提供。上述固体电解质可以通过上述壳聚糖含有大量的OH离子及水分,可以具有高离子导电率。
Smart Images

Figure CN115136390B_ABST
Abstract
Description
Technical Field
[0001] This application relates to composite fibers, solid electrolytes containing the same, and metal-air batteries containing the same. Background Technology
[0002] With the rapid development of secondary batteries for existing small devices and electronic products, and even for medium-to-large-scale high-energy applications such as electric vehicles and energy storage systems (ESS), the market value of the secondary battery industry was only about US$22 billion in 2018, but it is projected to increase to US$118 billion by 2025. For secondary batteries to be used as a medium for medium-to-large-scale energy storage, they need to achieve significantly higher price competitiveness, energy density, and stability than they currently possess.
[0003] Based on these technical requirements, research on secondary batteries utilizing solid electrolytes is actively underway.
[0004] For example, International Patent Publication No. WO2014200198A1 discloses a composite electrode-composite electrolyte composite, which is integrally formed of a composite electrode layer and a composite electrolyte layer. The composite electrode layer includes a current collector and an electrode mixture layer formed on the current collector. The mixture layer includes an electrode active material, a conductive material, a cross-linked polymer matrix, a dissociable salt, and an organic solvent. The composite electrolyte layer includes a cross-linked polymer matrix, inorganic particles, a dissociable salt, and an organic solvent. The electrode mixture layer and the composite electrolyte layer are overlapped to be physically bonded.
[0005] For example, Korean Patent Publication No. 10-1734301 discloses a method for preparing a solid electrolyte for lithium batteries, characterized by comprising: a first step of reacting a first metal precursor formed from a Li precursor, a second metal precursor formed from an Al precursor, a third metal precursor formed from a Ti precursor, and a P precursor with a chelating agent to prepare a sol; a second step of heating the sol to prepare a gel; a third step of heating the gel to thermally decompose it; a fourth step of heat-treating the thermally decomposed gel by contacting it with air; a fifth step of cooling the powder obtained in the fourth step; a sixth step of mixing the powder cooled in the fifth step with 0.2 to 1 wt% of a sintering aid Bi₂O₃; and a seventh step of pressing the mixed powder obtained in the sixth step into shape and sintering it at 850°C by contact with air, wherein the relative density (%) of the sintered body is 90.0 to 99.7 and the ionic conductivity (S cm⁻¹) is [not specified]. -1 The value is 7.9 × 10 -4 Up to 9.9×10 -4 . Summary of the Invention
[0006] Technical issues
[0007] One of the technical problems to be solved by this application is to provide a solid electrolyte with high reliability and high ionic conductivity and a metal-air battery containing the same.
[0008] Another technical problem to be solved by this application is to provide a long-life solid electrolyte and a metal-air battery containing the same.
[0009] Another technical problem to be solved by this application is to provide a flexible solid electrolyte with high mechanical stability and a metal-air battery containing the same.
[0010] Another technical problem to be solved by this application is to provide a metal-air battery with improved charge-discharge capacity and lifespan.
[0011] Another technical problem to be solved by this application is to provide composite fibers and membranes for solid electrolytes, as well as methods for their preparation.
[0012] Another technical problem to be solved by this application is to provide a solid electrolyte that can operate in high and low temperature environments and a method for preparing the same.
[0013] Another technical problem to be solved by this application is to provide a solid electrolyte that maintains high ionic conductivity in high and low temperature environments and a method for preparing the same.
[0014] Another technical problem to be solved by this application is to provide a solid electrolyte that is flexible and has high mechanical stability in high and low temperature environments, and a method for preparing the same.
[0015] Another technical problem to be solved by this application is to provide a metal-air battery containing a solid electrolyte that can operate in high and low temperature environments.
[0016] Another technical problem to be solved by this application is to provide a metal-air battery with high charge-discharge capacity and long life in high and low temperature environments.
[0017] The technical problem to be solved in this application is not limited to the above-mentioned issues.
[0018] Technical solution
[0019] To address the aforementioned technical problems, this application provides a solid electrolyte.
[0020] According to one embodiment, the solid electrolyte may comprise a basic composite fiber having bacterial cellulose and chitosan bound to the bacterial cellulose.
[0021] According to one embodiment, the above-mentioned basic composite fiber may contain a mixture of crystalline and amorphous phases.
[0022] According to one embodiment, the surface of the bacterial cellulose containing the chitosan can be oxidized.
[0023] According to one embodiment, the surface of the bacterial cellulose bound with the chitosan can be oxidized using an aqueous solution of 2,2,6,6-tetramethylpiperidine-1-oxy (TEMPO).
[0024] According to one embodiment, the surface of the bacterial cellulose containing the chitosan can be bound to a first functional group having nitrogen.
[0025] According to one embodiment, the first functional group described above can be represented by the following chemical formula 1.
[0026] Chemical Formula 1
[0027]
[0028] According to one embodiment, the solid electrolyte may comprise: a first composite fiber whose surface is oxidized; and a second composite fiber whose surface is bonded to a first functional group having nitrogen.
[0029] According to one embodiment, the proportion of the first composite fiber can be greater than 30% by weight and less than 70% by weight, and the proportion of the second composite fiber can be less than 70% by weight and greater than 30% by weight.
[0030] According to one embodiment, the first composite fiber and the second composite fiber can be cross-linked.
[0031] According to one embodiment, the solid electrolyte may comprise: a membrane containing cellulose; and chitosan, which is bound to the cellulose in the membrane in an amount greater than 30% by weight and less than 70% by weight.
[0032] According to one embodiment, when the chitosan content is 50% by weight, X-ray photoelectron spectroscopy (XPS) analysis shows that the proportion of CN bonds has a maximum value in the C1s spectrum.
[0033] According to one embodiment, the cellulose described above may comprise bacterial cellulose.
[0034] According to one embodiment, the crystallinity, ionic conductivity, and expansion ratio can be controlled based on the ratio of chitosan described above.
[0035] According to one embodiment, the higher the proportion of chitosan, the more gradually the crystallinity can be reduced.
[0036] To address the aforementioned technical problems, this application provides a method for preparing solid electrolytes.
[0037] According to one embodiment, the method for preparing the solid electrolyte may include: a step of preparing a chitosan derivative; a step of generating chitosan bound to cellulose from the chitosan derivative; and a step of preparing a solid electrolyte using the cellulose bound to the chitosan.
[0038] According to one embodiment, the crystallinity, ionic conductivity, and expansion ratio can be controlled based on the proportion of the chitosan derivatives described above.
[0039] According to one embodiment, the cellulose described above may comprise bacterial cellulose.
[0040] According to one embodiment, the step of generating the chitosan bound to the cellulose may include: preparing a culture medium containing the chitosan derivative; and injecting a bacterial strain into the culture medium and culturing it.
[0041] According to one embodiment, the method for preparing the above-mentioned solid electrolyte may further include: a step of preparing a first composite fiber by oxidizing the surface of the cellulose with chitosan bound by an oxidant; or a step of preparing a second composite fiber by replacing the bromine with a first functional group containing nitrogen after binding bromine to the surface of the cellulose with chitosan bound by oxidant.
[0042] According to one embodiment, the method for preparing the solid electrolyte may further include: a step of preparing a first composite fiber by oxidizing the surface of the cellulose with chitosan bound by an oxidant; a step of preparing a second composite fiber by replacing the bromine with a first functional group containing nitrogen after binding bromine to the surface of the cellulose with chitosan bound by it; and a step of crosslinking the first composite fiber and the second composite fiber.
[0043] The effects of the invention
[0044] The solid electrolyte of this application embodiment may comprise: a membrane containing cellulose; and chitosan, bonded to the cellulose in the membrane. The solid electrolyte can be provided in the form of a membrane network composed of the aforementioned basic composite fibers. The solid electrolyte can possess high ionic conductivity due to the presence of a large number of OH ions and water in the chitosan.
[0045] This can improve the charge / discharge capacity and lifespan characteristics of metal-air batteries containing the aforementioned solid electrolyte.
[0046] Furthermore, the aforementioned solid electrolyte can be prepared by injecting bacterial strains into a culture medium containing chitosan derivatives and then culturing them. This allows for an increase in the chitosan content of the solid electrolyte and makes it easier to control the chitosan content.
[0047] Therefore, the ionic conductivity, expansion ratio, and water immersion rate of the aforementioned solid electrolytes can be improved.
[0048] The metal-air battery containing the above-mentioned solid electrolyte can be charged and discharged at temperatures ranging from -20°C to 80°C. Accordingly, a solid electrolyte and a metal-air battery containing it that can be used stably in high and low temperature environments can be provided. Attached Figure Description
[0049] Figure 1 This is a flowchart illustrating the preparation method of the solid electrolyte in the embodiments of this application.
[0050] Figure 2 A diagram illustrating the basic composite fiber of an embodiment of this application.
[0051] Figure 3 A diagram illustrating the first composite fiber of an embodiment of this application.
[0052] Figure 4 A diagram illustrating the second composite fiber according to an embodiment of this application.
[0053] Figure 5 A diagram illustrating a solid electrolyte comprising the basic composite fiber of an embodiment of this application.
[0054] Figure 6 A diagram illustrating a metal-air battery incorporating a solid electrolyte according to an embodiment of this application.
[0055] Figure 7 The figure is used to illustrate the first composite fiber and its preparation method in Experimental Examples 1-2 of this application.
[0056] Figure 8 The figure is used to illustrate the second composite fiber and its preparation method in Experimental Examples 1-3 of this application.
[0057] Figure 9 This is a diagram illustrating the preparation method of the solid electrolytes in Experimental Examples 1-4 of this application.
[0058] Figure 10 This is a diagram illustrating the ion movement principle of the solid electrolytes in Experimental Examples 1-4 of this application.
[0059] Figure 11 The results of hydrogen nuclear magnetic resonance (NMR) analysis of the first composite fiber, the second composite fiber, and the solid electrolyte prepared according to Experimental Examples 1-2 to 1-4 of this application are shown.
[0060] Figure 12 The results of X-ray diffraction (XRD) analysis of solid electrolytes, bacterial cellulose, common bacterial cellulose and cellulose prepared according to Experimental Examples 1-4 to 1-7 of this application are as follows.
[0061] Figure 13 The Fourier transform infrared (FT-IR) spectroscopic analysis results are given for the solid electrolytes, bacterial cellulose and common bacterial cellulose prepared according to Experimental Examples 1-4 to 1-6 of this application.
[0062] Figure 14 To take scanning electron microscope (SEM) images of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0063] Figure 15 The results are based on thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analysis of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0064] Figures 16 to 19 The graphs show the X-ray photoelectron spectroscopy (XPS) results of solid electrolytes and bacterial cellulose in Experimental Examples 1-4 and 1-5 of this application.
[0065] Figure 20 The ionic conductivity measurement results are used to illustrate the alkali resistance test results of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0066] Figure 21 X-ray diffraction analysis results are used to illustrate the alkali resistance test results of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0067] Figure 22 The figure is used to illustrate the alkali resistance test results of the solid electrolytes in Experimental Examples 1-4 of this application.
[0068] Figure 23 The stress-strain curves of the water immersion rate of the solid electrolytes in Experimental Examples 1-4 of this application are shown.
[0069] Figure 24 The graph shows the results of measuring the ionic conductivity of the solid electrolytes in Experiment Examples 1-4 of this application under mechanical deformation.
[0070] Figure 25 The graphs are for measuring the storage modulus of the solid electrolytes in Experimental Examples 1-4 of this application.
[0071] Figure 26 This is a diagram illustrating the mechanical stability of the solid electrolytes in Experimental Examples 1-4 of this application.
[0072] Figure 27 The graphs are used to measure the ion transport rates of the solid electrolytes in Experimental Examples 1-4 of this application.
[0073] Figure 28The results are X-ray diffraction analysis results of the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0074] Figure 29 The Fourier transform infrared spectroscopy analysis results are for the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0075] Figure 30 The results were obtained for measuring the ionic conductivity of the solid electrolytes in Experimental Examples 2-1 to 2-55 of this application based on temperature.
[0076] Figure 31 The graphs were used to measure the water immersion rate and expansion ratio of the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0077] Figure 32 The Arrhenius plot shows the conductivity of the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0078] Figures 33 to 35 The results of X-ray photoelectron spectroscopy analysis of the solid electrolytes in Experimental Examples 3-1 to 3-5 and the bacterial cellulose in Experimental Examples 1-5 are as follows.
[0079] Figure 36 To analyze the elemental ratio curves of the solid electrolytes in Experimental Examples 3-1 to 3-5 and the bacterial cellulose in Experimental Examples 1-5 of this application.
[0080] Figure 37 The results were used to analyze the composition ratio of the C1s spectra of the solid electrolytes in Experimental Examples 3-1 to 3-5 and the bacterial cellulose in Experimental Examples 1-5 of this application.
[0081] Figure 38 The results were used to analyze the composition ratio of the N1s spectra of the solid electrolytes in Experimental Examples 3-1 to 3-5 and the bacterial cellulose in Experimental Examples 1-5 of this application.
[0082] Figure 39 The results are X-ray diffraction analysis of the solid electrolytes in Experimental Examples 3-1 to 3-5, the chitosan in Experimental Example 3-6, and the bacterial cellulose in Experimental Examples 1-5 of this application.
[0083] Figure 40 The results of measuring the ionic conductivity at temperature of the solid electrolytes in Experimental Examples 3-1 to 3-5, the chitosan in Experimental Example 3-6, the bacterial cellulose in Experimental Examples 1-5, and the ordinary bacterial cellulose in Experimental Examples 1-6 of this application are presented.
[0084] Figure 41The results were obtained by measuring the expansion ratio of solid electrolytes in Experimental Examples 3-1 to 3-5, chitosan in Experimental Example 3-6, bacterial cellulose in Experimental Examples 1-5, and ordinary bacterial cellulose in Experimental Examples 1-6 according to temperature.
[0085] Figure 42 The results were obtained by measuring the water immersion rate of the solid electrolytes in Experimental Examples 3-1 to 3-5, the chitosan in Experimental Example 3-6, the bacterial cellulose in Experimental Examples 1-5, and the ordinary bacterial cellulose in Experimental Examples 1-6.
[0086] Figure 43 This is a graph illustrating the results of measuring the voltage of the solid electrolyte in Experimental Examples 1-4 of this application.
[0087] Figure 44 This is a graph illustrating the charge-discharge capacity of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application.
[0088] Figure 45 The voltage values of metal-air batteries containing solid electrolytes from Experimental Examples 1-4 of this application are measured based on the number of charge-discharge cycles.
[0089] Figure 46 This is a graph illustrating the changes in charge-discharge characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application under external temperature conditions.
[0090] Figure 47 The graph illustrates the retention characteristics of metal-air batteries containing the solid electrolytes of Experimental Examples 1-4 of this application in low-temperature and high-temperature environments based on the number of charge-discharge cycles.
[0091] Figure 48 A graph illustrating the charge-discharge characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application, based on external temperature.
[0092] Figure 49 A graph illustrating the capacity characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application as a function of external temperature.
[0093] Figure 50 This is a graph illustrating the charge-discharge characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application under charge-discharge cycles at external temperature.
[0094] Figure 51 A block diagram illustrating an embodiment of the electric vehicle of the present invention. Detailed Implementation
[0095] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the technical concept of the present invention is not limited to the embodiments described herein, and can be embodied in other forms. The embodiments described herein are merely intended to make the disclosure thorough and complete, and to fully convey the spirit of the present invention to those skilled in the art.
[0096] In this specification, when a structural element is mentioned as being located on other structural elements, it means that it is formed directly on the other structural elements or that a third structural element may be inserted between them. Furthermore, in the accompanying drawings, the thickness of the membrane and the region is exaggerated for the purpose of effectively illustrating the technical content.
[0097] Furthermore, in the various embodiments of this specification, the terms "first," "second," "third," etc., are used only to describe various structural elements, which are not limited by these terms. These terms are only used to distinguish one structural element from others. Therefore, a first structural element mentioned in one embodiment may also be described as a second structural element in other embodiments. The embodiments described and illustrated herein also include complementary embodiments. Furthermore, the word "and / or" in this specification is used to mean including at least one of the structural elements listed above.
[0098] In this specification, unless otherwise explicitly stated in the context, singular expressions include plural expressions. Furthermore, terms such as "comprising" or "having" are used to indicate the presence of features, numbers, steps, structural elements, or combinations thereof described in the specification, and should not be construed as excluding the presence or additional possibilities of more than one other feature, number, structural element, or combination thereof. Moreover, in the following description of the invention, detailed descriptions of relevant well-known functions or structures will be omitted when it is determined that such detailed descriptions would unnecessarily obscure the essence of the invention.
[0099] Figure 1 This is a flowchart illustrating the preparation method of the solid electrolyte in the embodiments of this application. Figure 2 A diagram illustrating the basic composite fiber of an embodiment of this application, Figure 3 A diagram illustrating the first composite fiber of an embodiment of this application, Figure 4 A diagram illustrating the second composite fiber according to an embodiment of this application, Figure 5 A diagram illustrating a solid electrolyte comprising the basic composite fiber of an embodiment of this application.
[0100] Reference Figures 1 to 5 Prepare chitosan derivatives (step S110).
[0101] The chitosan derivatives described above can be in the form of a chitosan precursor mixed with a solvent. According to one embodiment, the chitosan derivatives can be in the form of chitosan chloride and a solvent with a solvent added. Accordingly, the chitosan chloride can be readily soluble in the solvent, and the chitosan derivatives can be readily provided to the culture medium described later, thereby easily preparing cellulose conjugated with chitosan.
[0102] For example, the solvent may be aqueous acetic acid, and the solvent may contain at least one of glycidyl trimethylammonium chloride, (2-aminoethyl)trimethylammonium chloride, (2-chloroethyl)trimethylammonium chloride, (3-carboxypropyl)trimethylammonium chloride, or (formylmethyl)trimethylammonium chloride.
[0103] The chitosan described above exhibits excellent thermal and chemical stability, high ionic conductivity, and can retain OH ions for extended periods without loss. Furthermore, as described later, it demonstrates high interchangeability with zinc anodes and compounds of copper, phosphorus, and sulfur when used in metal-air batteries.
[0104] Chitosan bound to cellulose is generated from the chitosan derivative described above (step S120). The step of generating the cellulose bound to the chitosan may include: preparing a culture medium containing the chitosan derivative; and injecting a bacterial strain into the culture medium and culturing it to prepare a basic composite fiber 110 containing cellulose 112 bound to chitosan 114. In this case, the cellulose 112 may be bacterial cellulose.
[0105] According to one embodiment, the cellulose 112 incorporating the chitosan 114 can be prepared by desalting the bacterial membrane after culturing it in the culture medium. The bacterial membrane can be prepared by culturing a culture medium containing the chitosan derivative along with yeast and raw materials for culturing bacteria (e.g., pineapple juice, peptone, disodium hydrogen phosphate, citric acid), and then inoculating the culture with a bacterial strain. For example, the bacterial strain can be *Acetobacter xylinum*.
[0106] After washing and drying the bacterial membranes cultured above, the above-mentioned basic composite fiber 110 containing the above-mentioned cellulose 112 bound with chitosan 114 can be prepared by desalting with an acidic solution (e.g., HCl), neutralizing, and removing the solvent. During the desalting process, residual Na, K, or cell covering material and debris can be removed to prepare high-purity cellulose 112 bound with chitosan 114.
[0107] Furthermore, the chitosan 114 can form a chemical bond with the cellulose 112. Accordingly, the cellulose 112 with chitosan 114 bonded to it can be observed to exhibit stretching vibrations corresponding to CN during X-ray photoelectron spectroscopy analysis.
[0108] According to one embodiment, the surface of the cellulose 112 with chitosan 114 bonded thereto can be oxidized by an oxidant, that is, the surface of the basic composite fiber 110 can be oxidized to prepare the first composite fiber 110a.
[0109] Specifically, the steps for preparing the first composite fiber 110a may include: adding the base composite fiber 110 to an aqueous solution containing an oxidant to prepare a source solution; adjusting the pH of the source solution to alkaline; adjusting the pH of the source solution to neutral; and washing and drying the slurry in the source solution to prepare the first composite fiber 110a.
[0110] For example, the aqueous solution containing the oxidant described above can be an aqueous solution of 2,2,6,6-tetramethylpiperidine-1-oxy. Alternatively, as another example, the aqueous solution containing the oxidant described above can contain 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy (4-Hydroxy-TEMPO), (Diacetoxyiodo)benzene, 4-amino-2,2,6,6-tetramethylpiperidine-1-oxy (4-Amino-TEMPO), 4-carboxy-2,2,6,6-tetramethylpiperidine-1-oxy (4-Carboxy-TEMPO), 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxy (4-Methoxy-TEMPO), or 2,2,6,6-tetramethylpiperidine-1-oxymethacrylate (TEMPO). It is at least one of the following: methacrylate, 4-acetamido-1-oxy, 3-carboxy-1-methylpyrrolidine-1-oxy, 4-maleimido-1-oxy, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxybenzoate, or 4-phosphonooxy-2,2,6,6-tetramethylpiperidine-1-oxy.
[0111] The aforementioned source solution may also contain a sacrificial agent and an additional oxidant for the oxidation reaction of the aforementioned basic composite fiber 110. The sacrificial agent may contain at least one of NaBr, sodium iodide, sodium bromate, sodium bromite, sodium borate, sodium chlorite, or sodium chloride. The additional oxidant may contain at least one of NaClO, potassium hypochlorite, lithium hypochlorite, sodium chlorite, perchloric acid, potassium perchlorate, lithium perchlorate, tetrabutylammonium perchlorate, zinc perchlorate, hydrogen peroxide, or sodium peroxide.
[0112] According to one embodiment, in the step of adjusting the pH of the source solution to alkaline, the pH of the source solution can be adjusted to 10. Accordingly, the oxidation reaction can be easily induced while minimizing precipitates, and the oxidation degree of the first composite fiber 110a can be increased compared to reaction conditions with a pH of 8-9.
[0113] According to one embodiment, the additional oxidant can be provided after the basic composite fiber 110 and the sacrificial agent are provided to the aqueous solution containing the oxidant. Furthermore, the additional oxidant can be provided dropwise. Accordingly, severe oxidation of the basic composite fiber 110 can be prevented, resulting in uniform and stable oxidation of the surface of the basic composite fiber 110.
[0114] Furthermore, according to one embodiment, a second composite fiber 110b can be prepared by replacing bromine with a nitrogen-containing first functional group 116 after bromine is bound to the surface of the cellulose 112 which is bonded with chitosan 114.
[0115] The first functional group 116 can be represented by the following chemical formula 1, and the first functional group 116 can be combined with the chitosan 114 and / or the cellulose 112.
[0116] Chemical Formula 1
[0117]
[0118] That is, the second composite fiber 110b mentioned above can have quaternary nitrogen.
[0119] Specifically, the steps for preparing the second composite fiber 110b may include: dispersing the basic composite fiber 110 in a first solvent and then adding a bromine source to prepare a first source solution; adding a coupling agent to the first source solution to prepare a reaction suspension; filtering, washing, and freeze-drying the reaction suspension to prepare a brominated basic composite fiber; dispersing the brominated basic composite fiber in a second solvent to prepare a second source solution; adding the first functional group 116 precursor to the second source solution to react; and filtering, washing, and freeze-drying the reaction solution to prepare the second composite fiber 110b.
[0120] For example, the first solvent and the second solvent described above may be the same, and may contain at least one of N,N-dimethylacetamide, acetamide, acetonitrile, ethanol, ethylenediamine, diethyl ether, or benzaldehyde.
[0121] For example, the bromine source mentioned above may include at least one of LiBr, sodium bromide, or potassium bromide.
[0122] For example, the coupling agent described above may contain N-bromosuccinimide and triphenylphosphine. This coupling agent allows bromine to readily bind to the surface of the basic composite fiber 110. Specifically, the bromine within the N-bromosuccinimide can bind to the basic composite fiber 110, and the triphenylphosphine can reduce the bromine precursor (bromine source or N-bromosuccinimide) to increase the reaction rate.
[0123] As described above, after obtaining the brominated basic composite fiber from the above reaction suspension, the brominated basic composite fiber can be freeze-dried. This minimizes the loss of bromine in the brominated basic composite fiber and minimizes the possibility of secondary reactions between bromine and other elements.
[0124] For example, the aforementioned first functional group 116 precursor may contain 1,4-diazabicyclo[2.2.2]octane.
[0125] Solid electrolytes can be prepared using the cellulose 112 incorporating the chitosan 114 described above (step S130).
[0126] like Figure 5 As shown, the solid electrolyte can be prepared as a membrane comprising the basic composite fiber 110 containing the cellulose 112 incorporating the chitosan 114. Therefore, the solid electrolyte can provide multiple pores internally and has a high surface area, exhibiting excellent flexibility and mechanical properties.
[0127] The aforementioned solid electrolyte can exist in a mixture of crystalline and amorphous phases. More specifically, the proportion of the amorphous phase in the solid electrolyte can be higher than the proportion of the crystalline phase. Accordingly, the aforementioned solid electrolyte can possess high ion mobility.
[0128] Furthermore, when the aforementioned solid electrolyte is installed in a metal-air battery, the metal-air battery can smoothly perform charge and discharge operations at temperatures ranging from -20°C to 80°C. That is, the metal-air battery incorporating the solid electrolyte described in this application embodiment can operate smoothly at both low and high temperatures, has a wide operating temperature range, and can be used in various environments.
[0129] According to one embodiment, the solid electrolyte can be prepared using a gelatin process involving the first composite fiber 110a and the second composite fiber 110b. In this case, the solid electrolyte may comprise the first composite fiber 110a and the second composite fiber 110b, which are cross-linked together. The first composite fiber 110a can increase the number of OH ions in the solid electrolyte and improve ionic conductivity, thereby increasing negative charge density and anti-swelling properties. Furthermore, the second composite fiber 110b can increase molecular weight to improve thermal stability, enhance ion exchange capacity for high water solubility and high anti-swelling properties, improve cross-linking bonding with the first composite fiber 110a, and selectively exhibit high solubility in specific solvents (ion discerning selectivity). Accordingly, the charge / discharge characteristics and lifespan characteristics of the secondary battery containing the solid electrolyte can be improved.
[0130] Specifically, the steps for preparing the above-mentioned solid electrolyte may include: mixing the above-mentioned first composite fiber 110a and the above-mentioned second composite fiber 110b in a solvent to prepare a mixed solution; adding a crosslinking agent and an initiator to the above-mentioned mixed solution and reacting to prepare a suspension; pouring the above-mentioned suspension onto a substrate and drying it to prepare a composite fiber membrane; and performing an ion exchange process on the above-mentioned composite fiber membrane.
[0131] For example, the solvent may include a mixture of dichloromethane, 1,2-propanediol and acetone; the crosslinking agent may include glutaraldehyde; and the initiator may include N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide.
[0132] Furthermore, for example, the ion exchange process for the aforementioned composite fiber membrane may include the step of providing the composite fiber membrane with an aqueous solution of KOH and an aqueous solution of ZnTFSI. Therefore, the OH ion content within the aforementioned solid electrolyte can be increased.
[0133] As described above, according to the embodiments of this application, the solid electrolyte may include the membrane M, and the membrane M may include at least one of the basic composite fiber 110, the first composite fiber 110a, or the second composite fiber 110b.
[0134] Within the aforementioned solid electrolyte, the proportion of chitosan 114 can be easily controlled based on the content of the chitosan derivative supplied to the culture medium. The crystallinity, ionic conductivity, and expansion ratio of the solid electrolyte can be controlled based on the proportion of chitosan 114. Specifically, the higher the proportion of chitosan 114, the more gradually the crystallinity of the solid electrolyte can decrease.
[0135] According to one embodiment, the content of chitosan 114 can be greater than 30% by weight and less than 70% by weight. If the content of chitosan 114 is less than 30% by weight or more than 70% by weight, the ionic conductivity of the solid electrolyte can be significantly reduced, and the expansion ratio can be significantly increased.
[0136] However, according to the embodiments of this application, the proportion of chitosan 114 in the solid electrolyte can be greater than 30% by weight and less than 70% by weight. Therefore, the solid electrolyte can maintain high ionic conductivity while having a low expansion ratio.
[0137] Figure 6 A diagram illustrating a metal-air battery incorporating a solid electrolyte according to an embodiment of this application.
[0138] Reference Figure 6 This application provides a metal-air battery according to an embodiment of the present application. The metal-air battery may include a negative electrode 200, a positive electrode 300, and a solid electrolyte 100 between the negative electrode 200 and the positive electrode 300.
[0139] The aforementioned solid electrolyte 100 can provide unreferenced... Figures 1 to 5 The membrane morphology described includes at least one of the above-mentioned basic composite fiber 110, the above-mentioned first composite fiber 110a, or the above-mentioned second composite fiber 110b.
[0140] The aforementioned negative electrode 200 may contain zinc. Alternatively, the aforementioned negative electrode 200 may contain lithium.
[0141] According to one embodiment, the above-mentioned positive electrode 300 may comprise Pt / C and RuO2. Alternatively, according to other embodiments, the above-mentioned positive electrode 300 may comprise a compound structure of copper, phosphorus, and sulfur. In this case, the above-mentioned copper, phosphorus, and sulfur compound structure can be provided as a morphology of a film composed of multiple fibrous fibers, and may have (101) crystal planes. The specific preparation process of the above-mentioned copper, phosphorus, and sulfur compound structure will be referred to Figure 41 This will be explained in the following section.
[0142] The solid electrolyte 100 contained in the metal-air battery of this application embodiment contains a large amount of OH ions and water, and can have high ionic conductivity. Therefore, not only can the charge / discharge capacity and lifespan characteristics of the metal-air battery be improved, but the growth of dendrites on the surface of the negative electrode 200 can also be minimized during the charge / discharge process of the metal-air battery.
[0143] The solid electrolytes of this application embodiment can be circulated, transported, traded, and stored in various forms as intermediate products. The following describes various forms of intermediate products used to prepare the solid electrolytes of this application embodiment.
[0144] According to the first modified example, in the case of omitting the chitosan derivative and the desalting process according to Experimental Examples 1-5 described later, and using bacterial cellulose that does not contain chitosan, it can be in a gel state immediately after synthesis, or in a solid state (powder) after drying, or in a solution state provided to the solvent. For example, the solvent can be deionized water (DI water) or an organic solvent (e.g., dichloromethane, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), tetrahydrofuran (THF), isopropanol (IPA)).
[0145] According to the second variation, in the case of the chitosan derivative of the above-described embodiments of this application, it can be in a gel state immediately after synthesis, or in a solid state (powder) after drying, or in a solution state provided to a solvent. For example, the solvent can be deionized water or ethanol.
[0146] According to the third variation, in the case of the basic composite fiber 110 containing chitosan-infused cellulose from the embodiments of this application, it can be in a gel state immediately after synthesis, or in a solid state (powder) after drying, or in a solution state provided to a solvent. For example, the solvent can be deionized water, dimethyl sulfoxide, ethanol, dichloromethane, isopropanol, N,N-dimethylformamide, or tetrahydrofuran.
[0147] According to the fourth variation, in the case where the surface of the first composite fiber 110a of the basic composite fiber 110 in the above-described embodiments of this application is oxidized, it can be in a gel state immediately after synthesis, or in a solid state (powder) after drying, or in a solution state provided to a solvent. For example, the solvent can be CHCl3 or dimethyl sulfoxide.
[0148] According to the fifth variation, in the case of the brominated basic composite fiber with bromine bonded to the surface of the basic composite fiber 110 in the above-described embodiments of this application, it can be in a gel state immediately after synthesis, or in a solid state (powder) after drying, or in a solution state provided to a solvent. For example, the solvent can be CHCl3, dimethyl sulfoxide, or ethanol.
[0149] According to the sixth variation, in the case of the second composite fiber 110b having the first functional group of the present application bonded to the quaternary nitrogen on the surface of the basic composite fiber 110, it can be in a gel state immediately after synthesis, or in a solid state (powder) after drying, or in a solution state provided to a solvent. For example, the solvent can be CHCl3 or dimethyl sulfoxide.
[0150] According to the seventh variation, in the case of the solid electrolyte in which the first composite fiber 110a and the second composite fiber 110b are crosslinked according to the embodiments of this application, it may have a solid state (membrane) or a solution state provided to a solvent. For example, the solvent may be CHCl3 or dimethyl sulfoxide.
[0151] The following describes the preparation methods of the basic composite fiber, the first composite fiber, the second composite fiber, and the solid electrolyte in specific experimental examples of this application.
[0152] Figure 7 The figures are for illustrating the first composite fiber and its preparation method in Experimental Examples 1-2 of this application. Figure 8 The figures are for illustrating the second composite fiber and its preparation method in Experimental Examples 1-3 of this application. Figure 9 The figures are for illustrating the preparation method of the solid electrolytes in Experimental Examples 1-4 of this application. Figure 10 This is a diagram illustrating the ion movement principle of the solid electrolytes in Experimental Examples 1-4 of this application.
[0153] Preparation of the basic composite fiber (CBC) in Experiment 1-1
[0154] Prepare *Acetobacter xylinum* as the bacterial strain and prepare chitosan derivatives. The chitosan derivatives were prepared as follows: 1 g of chitosan chloride was dissolved in a suspension of 1% (v / v) aqueous acetic acid for 24 hours under a N2 atmosphere at 65°C using 1M glycidyltrimethylammonium chloride. After precipitation, the solution was filtered multiple times with ethanol.
[0155] After preparing Hestrin-Schramm (HS) medium containing pineapple juice (2%, w / v), yeast (0.5%, w / v), peptone (0.5%, w / v), disodium hydrogen phosphate (0.27%, w / v), citric acid (0.015%, w / v), and the aforementioned chitosan derivative (2%, w / v), the medium was steam-sterilized at 121°C for 20 minutes. Furthermore, after activating *Acetobacter xylinum* in pre-cultivated Hestrin-Schramm (HS) medium at 30°C for 24 hours, acetic acid was added to maintain the pH at 6.
[0156] Then, Acetobacter xylinum was cultured in Hestrin-Schramm (HS) medium at 30°C for 7 days.
[0157] The obtained bacterial pellicles were washed with deionized water, and the supernatant was neutralized. The supernatant was then dehydrated under vacuum at 105°C. Excess reagent was removed by demineralizing the resulting cellulose with 1N HCl for 30 minutes (1:15, w / v). The cellulose was then purified by repeated centrifugation with deionized water until the supernatant reached neutral pH. Finally, the basic composite fiber (chitosan-bacterial cellulose (CBC)) was prepared by evaporating all solvents at 100°C.
[0158] Preparation of the first composite fiber (oCBC) in Experimental Example 1-2
[0159] like Figure 7 As shown, the first composite fiber (2,2,6,6-tetramethylpiperidine-1-oxy-oxidized CBCs (oCBCs)) whose surface is oxidized is achieved by means of an oxidation reaction of 2,2,6,6-tetramethylpiperidine-1-oxy (TEMPO), sodium bromide (NaBr), and sodium hypochlorite (NaClO) to conjugate the hydroxymethyl and ortho-paradirecting acetamido basic composite fiber (CBC) with the oxide of 2,2,6,6-tetramethylpiperidine-1-oxy.
[0160] Specifically, 2 g of the basic composite fiber, dispersed in a 2 mM aqueous solution of 2,2,6,6-tetramethylpiperidine-1-oxy, was reacted with NaBr (1.9 mM). 5 mM NaClO was used as an additional oxidant.
[0161] After ultrasonic stirring of the reaction suspension, the reaction was carried out at room temperature for 3 hours. The pH of the suspension was maintained at 10 by continuously adding 0.5M NaOH solution. Then, 1N HCl was added to the suspension to maintain the pH neutral for 3 hours. The oxidized slurry formed in the suspension was washed three times with 0.5N HCl, and the supernatant was neutralized with deionized water.
[0162] Within 30 minutes, acetone and toluene are replaced with the washed slurry and dried to evaporate the solvent, ultimately yielding the first composite fiber (oCBC).
[0163] exist Figure 7 As can be seen from this, the surface of the aforementioned basic composite fiber can be oxidized.
[0164] Preparation of the second composite fiber (qCBC) in Experiments 1-3
[0165] like Figure 8 As shown, the basic composite fiber combined with the second composite fiber (covalently quaternized CBC, qCBC) having a nitrogen-containing first functional group is prepared by using a coupling agent of 1,4-diazabicyclo[2.2.2]octane to conjugate the brominated basic composite fiber (CBC) with the quaternary ammonium group.
[0166] Specifically, 1 g of the basic composite fiber, dispersed in N,N-dimethylacetamide (35 ml) solution, was reacted with a LiBr (1.25 g) suspension for 30 minutes. N-bromosuccinimide (2.1 g) and triphenylphosphine (3.2 g) were used as coupling agents. After stirring the two reaction mixtures for 10 minutes, the reaction was carried out at 80 °C for 60 minutes.
[0167] Next, after cooling the reaction suspension at room temperature, deionized water was added, filtered, rinsed with deionized water and ethanol, and freeze-dried to obtain brominated basic composite fibers (bCBC).
[0168] The brominated basic composite fiber was dissolved in 100 ml of N,N-dimethylacetamide and then reacted with 1.2 g of 1,4-diazabicyclo[2.2.2]octane.
[0169] The mixture was then treated with ultrasound for 30 minutes and reacted at room temperature for 24 hours. The resulting solution was mixed with diethyl ether, washed five times with diethyl ether / ethyl acetate, and then freeze-dried to obtain the second composite fiber (covalently quaternized basic composite fiber (qCBC)).
[0170] exist Figure 8 It can be confirmed that the surface of the above-mentioned basic composite fiber is bonded with a first functional group having nitrogen.
[0171] Preparation of solid electrolytes (CBCs) in Examples 1-4
[0172] like Figure 8 As shown, the solid electrolyte is prepared using a gelatin process with the first composite fiber (oCBC) and the second composite fiber (qCBC) described above. Specifically, the first composite fiber (oCBC) and the second composite fiber (qCBC) are dissolved in a mixture of dichloromethane, 1,2-propanediol, and acetone (8:1:1, v / v / v%) using ultrasound in the same weight ratio. Then, 1% by weight of glutaraldehyde as a crosslinking agent and 0.3% by weight of N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide as an initiator are added.
[0173] After removing air bubbles from the gel suspension using a vacuum chamber (200 Pa), it was poured onto a glass surface at 60°C for 6 hours. The composite fiber membrane was then coagulated and peeled off using deionized water, rinsed with deionized water, and then vacuum dried.
[0174] Solid electrolytes (CBCs) were prepared by ion exchange with 1M KOH aqueous solution and 0.1M ZnTFSI for 6 hours at room temperature. Then, to avoid reaction with CO2 and formation of carbonates, a washing and impregnation process was performed with deionized water under N2 atmosphere.
[0175] exist Figure 9 It can be confirmed that the first composite fiber (oCBC) and the second composite fiber (qCBC) are cross-linked and combined to form the solid electrolyte (CBCs).
[0176] Furthermore, referring to Figure 10 OH ions can hop (or Grotthuss transport) on the surfaces of the first composite fiber (oCBC) and the second composite fiber (qCBC) crosslinked with the aforementioned solid electrolytes (CBCs), and can also move through diffusion within the interior separated from the surfaces of the first and second composite fibers. Furthermore, as referenced... Figure 12 As will be described later, the aforementioned solid electrolytes (CBCs) can have an amorphous phase, which can have higher ionic conductivity compared to crystalline structures.
[0177] Preparation of bacterial cellulose in Experiments 1-5
[0178] In the preparation method of the basic composite fiber in Experiment 1-1 above, the chitosan derivative and the desalting process are omitted, and bacterial cellulose without chitosan is prepared.
[0179] Preparation of common bacterial cellulose in Experiments 1-6
[0180] Bacterial cellulose was prepared using a culture medium containing glucose (2% by weight), peptone (0.5% by weight), yeast (0.5% by weight), disodium hydrogen phosphate (0.2% by weight), and citric acid (0.1% by weight), omitting the chitosan derivative and the desalting process, in the same manner as in Experimental Example 1-1.
[0181] Preparation of cellulose in Experimental Examples 1-7
[0182] After preparing the bagasse, prepare a solvent by mixing deionized water, NaOH, and nitric acid in ethanol. Disperse the bagasse in the solvent for washing, then filter and wash with deionized water until the pH reaches neutral.
[0183] After drying sugarcane bagasse at 100°C for 3 hours, fiber pulp was prepared by grinding it in the stainless steel body of a 16-mesh IKA MF-10 mill.
[0184] Cellulose was prepared by repeating the unit process of bleaching the fiber slurry with hydrogen peroxide (1%, pH 13.5) at 55°C for 1 hour three times, removing the residue with NaOH solution in an atmospheric atmosphere for 3 hours, washing with ethanol and acetone, and drying at 50°C for 6 hours.
[0185] The experimental examples 1-1 to 1-7 are summarized in Table 1 below.
[0186] Table 1
[0187]
[0188] Figure 11 The results of hydrogen nuclear magnetic resonance analysis of the first composite fiber, the second composite fiber, and the solid electrolyte prepared according to Experimental Examples 1-2 to 1-4 of this application are shown.
[0189] Reference Figure 11 The first composite fiber, the second composite fiber, and the solid electrolyte prepared according to Experimental Examples 1-2 to 1-4 above were analyzed by hydrogen analysis.
[0190] Figure 11 The circles marked with numbers in the analysis results and Figure 9 The hydrogen atoms in the circles marked with the same number correspond to each other. That is, it is possible to... Figure 11 China confirms Figure 9 The results of nuclear magnetic resonance analysis of the circles marked with numbers. Figure 11 It can be confirmed that the first composite fiber and the second composite fiber are cross-linked and repeatedly cross-linked in the same proportion.
[0191] Figure 12 The results of X-ray diffraction analysis of solid electrolytes, bacterial cellulose, common bacterial cellulose and cellulose prepared according to Experimental Examples 1-4 to 1-7 of this application are shown.
[0192] Reference Figure 12 X-ray diffraction analysis was performed on the solid electrolytes, bacterial cellulose, common bacterial cellulose and cellulose prepared according to Experimental Examples 1-4 to 1-7 above.
[0193] exist Figure 12It can be seen that the cellulose fibers of Experimental Examples 1-7 have high crystallinity and a hexagonal crystal structure with peaks corresponding to the (200), (110), and (1-10) crystal planes. In contrast, it can be seen that the crystallinity of bacterial cellulose (C(I)) of Experimental Examples 1-6 is relatively reduced, and the 2θ value of the peak corresponding to the (200) crystal plane is reduced.
[0194] Compared with the ordinary cellulose fibers of Examples 1-7, the crystallinity of the bacterial cellulose prepared according to the embodiments of this application is significantly reduced. Unlike the ordinary cellulose fibers of Examples 1-7 and the ordinary bacterial cellulose of Examples 1-6, it can be confirmed that there are peaks corresponding to the (020) and (110) crystal planes, and two peaks corresponding to the (1-10) crystal plane. Furthermore, it can be confirmed that the peak corresponding to the (110) crystal plane is higher than the peaks corresponding to other crystal planes (e.g., (101), (1-10)).
[0195] Furthermore, the solid electrolytes prepared according to Examples 1-4 of this application have both crystalline and amorphous phases, and it can be confirmed that the proportion of amorphous phase is significantly high.
[0196] Figure 13 Fourier transform infrared spectroscopy analysis results of solid electrolytes, bacterial cellulose and common bacterial cellulose prepared according to Experimental Examples 1-4 to 1-6 of this application.
[0197] Reference Figure 13 Fourier transform infrared spectroscopy analysis was performed on the solid electrolytes, bacterial cellulose and ordinary bacterial cellulose prepared according to Experimental Examples 1-4 to 1-6 above.
[0198] exist Figure 13 As can be seen from this, compared with the ordinary bacterial cellulose of Experiments 1-6, it can be confirmed that the stretching vibrations of CO and OH in the bacterial cellulose of Experiments 1-5 increased from 1056 cm⁻¹. -1 and 2932cm -1 Towards 1022cm -1 and 2895cm -1 Movement. Furthermore, in the case of the solid electrolyte in Experimental Examples 1-4 of this application, at 1458 cm⁻¹... -1 CN was observed + Stretching vibrations confirm the occurrence of quaternization. 2916 cm⁻¹ -1 and 3320cm -1 The vibration in the middle corresponds to the stretching vibration of OH, 1652 cm. -1 and 1750cm -1Corresponding to water, it can be confirmed that amorphous solid electrolytes contain sufficient water. The increased stretching vibration intensity of CO in the solid electrolytes of Examples 1-4 indicates the reaction between chitosan and bacterial cellulose. Furthermore, it can be confirmed that the solid electrolytes of Examples 1-4 are substantially free of carbonates, thus confirming their advantage over commercially available polyvinyl alcohol (PVA) electrolytes.
[0199] Figure 14 To take scanning electron microscope (SEM) images of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0200] Reference Figure 14 Scanning electron microscope images of the solid electrolytes prepared according to Experimental Examples 1-4 were taken.
[0201] exist Figure 14 It can be seen that there are multiple pores inside, which are provided in a fibrous form by chitosan bacterial cellulose fibers with a diameter of 5nm to 10nm.
[0202] The measured pore size is approximately 20 nm to 200 nm, indicating that bacterial cellulose bound with chitosan forms a network with high porosity and high surface area in a solid electrolyte, which can have high strength to resist expansion.
[0203] Figure 15 The results are based on thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analysis of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0204] Reference Figure 15 Thermogravimetric analysis and differential scanning calorimetry analysis were performed on the solid electrolytes prepared according to Experimental Examples 1-4 above under nitrogen atmosphere with a heating rate of 5 °C / min.
[0205] exist Figure 15 As can be seen from this, the solid electrolytes of Experimental Examples 1-4 of this application have thermal stability at a temperature of approximately 225°C. That is, it can be seen that the solid electrolytes prepared according to the embodiments of the present invention have high-temperature stability.
[0206] Figures 16 to 19 The graphs show the X-ray photoelectron spectroscopy (XPS) results of solid electrolytes and bacterial cellulose in Experimental Examples 1-4 and 1-5 of this application.
[0207] Reference Figures 16 to 19 X-ray photoelectron spectroscopy analysis was performed on the solid electrolytes and bacterial cellulose prepared according to Experimental Examples 1-4 and 1-5 above. Figure 17 The spectrum is C1s. Figure 18 The spectrum is N1s. Figure 19 This is the O1s spectrum.
[0208] exist Figure 17 In the above, 284.5 eV, 285.9 eV, 288 eV, and 289.7 eV correspond to C=C, CN, CO, and C-OH, respectively. Figure 18 In this context, 399.9 eV, 401.3 eV, and 402.5 eV correspond to pyrrolic, quaternary, and oxidized N, respectively.
[0209] exist Figures 16 to 19 As can be seen from the results, compared with the bacterial cellulose of Experimental Examples 1-5 which omitted chitosan, the X-ray photoelectron spectroscopy analysis of the solid electrolyte of Experimental Examples 1-4 which contained chitosan showed peaks in the N1s spectrum corresponding to pyrrole, quaternary ammonium and nitrogen oxides.
[0210] Figure 20 The ionic conductivity measurement results are used to illustrate the alkali resistance test results of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0211] Reference Figure 20 The solid electrolyte, polyvinyl alcohol film, and A201 membrane (Tokuyama Corporation) prepared according to Experimental Examples 1-4 above were immersed in 1M KOH solution at 100°C, and the ionic conductivity was measured over a period of 2500 hours. Figure 20 The inserted image is a photograph of the solid electrolyte (30cm × 30cm, 5μm) prepared according to Experimental Examples 1-4 of this application.
[0212] exist Figure 20 As can be seen from the results, it can be confirmed that the solid electrolytes in Experimental Examples 1-4 of this application do not substantially change in ionic conductivity. In contrast, it can be confirmed that the ionic conductivity of the A201 membrane and the polyvinyl alcohol film decreases sharply. That is, it can be confirmed that the solid electrolytes of the embodiments of this application do not change in ionic conductivity even when used in an alkaline environment, and have long-term reliability.
[0213] Figure 21 X-ray diffraction analysis results are used to illustrate the alkali resistance test results of the solid electrolytes prepared according to Experimental Examples 1-4 of this application.
[0214] Reference Figure 21 , as reference Figure 20 As can be seen, the solid electrolytes of Experiments 1-4 were immersed in KOH solution and then subjected to X-ray diffraction analysis.
[0215] exist Figure 21As can be seen from this, it can be confirmed that even after prolonged immersion in an alkaline solution, there is no substantial crystallographic change in the solid electrolyte. That is, it can be confirmed that the solid electrolyte of this application embodiment does not undergo crystallographic change even when used in an alkaline environment, and has long-term reliability.
[0216] Figure 22 The figure is used to illustrate the alkali resistance test results of the solid electrolytes in Experimental Examples 1-4 of this application.
[0217] Reference Figure 22 , as reference Figure 20 The images are shown below, showing the solid electrolytes from Experiments 1-4 immersed in KOH solution.
[0218] exist Figure 22 As can be seen from this, it can be confirmed that even after long-term immersion in alkaline solution, there is no substantial change in appearance of the solid electrolyte. That is, it can be confirmed that the solid electrolyte of this application embodiment does not change in appearance even when used in an alkaline environment and has long-term reliability.
[0219] Figure 23 The stress-strain curves of the water immersion rate of the solid electrolytes in Experimental Examples 1-4 of this application are shown.
[0220] Reference Figure 23 Stress-strain analysis of the water immersion rate of the solid electrolytes (CBCs) prepared according to Experimental Examples 1-4 above was performed at room temperature and 40% relative humidity. Stress-strain analysis was also performed on the A201 membrane (water immersion rate 44% by weight) under the same conditions.
[0221] exist Figure 23 It can be confirmed that the strain value of the applied stress varies with the water immersion rate. Specifically, it can be confirmed that the yield strength decreases as the water immersion rate increases.
[0222] In particular, compared with commercially available A201 membranes, it can be confirmed that the solid electrolyte of the experimental examples in this application has significantly higher mechanical properties while having significantly higher water immersion rate.
[0223] Figure 24 The graph shows the results of measuring the ionic conductivity of the solid electrolytes in Experiment Examples 1-4 of this application under mechanical deformation.
[0224] Reference Figure 24 The ionic conductivity of the solid electrolytes (CBCs) and A201 membranes prepared according to Experimental Examples 1-4 above was measured after being bent from 0 degrees to 180 degrees, and after being wrinkled or rolled up.
[0225] exist Figure 24As can be seen from this, the solid electrolytes prepared according to Experimental Examples 1-4 of this application do not show substantial changes in ionic conductivity even under various mechanical deformations. In contrast, it can be confirmed that the ionic conductivity of commercially available A201 membranes decreases with increasing number of bends, and drops sharply when wrinkled or rolled up.
[0226] That is, it can be confirmed that the solid electrolyte in the experimental examples of this application does not show substantial changes in ionic conductivity even under various mechanical deformations, and maintains stable performance.
[0227] Figure 25 The graphs are for measuring the storage modulus of the solid electrolytes in Experimental Examples 1-4 of this application.
[0228] Reference Figure 25 The storage modulus was measured by varying the frequency at which an external force was applied to the solid electrolyte prepared according to Experimental Examples 1-4 above. Figure 25 As can be seen from this, it can be confirmed that the storage modulus of the solid electrolyte increases linearly with increasing frequency.
[0229] Figure 26 This is a diagram illustrating the mechanical stability of the solid electrolytes in Experimental Examples 1-4 of this application.
[0230] Reference Figure 26 At room temperature ( Figure 26 Parts a, b, and c) and -20℃ Figure 26 The solid electrolyte prepared according to Experimental Examples 1-4 was wrinkled at the temperature of parts d, e, and f above, and then photographed to see if it recovered. Figure 26 As can be seen, it can be confirmed that regardless of whether it is at room temperature or low temperature, after being wrinkled, it easily returns to its original state. That is, it can be confirmed that the solid electrolytes of Experimental Examples 1-4 of this application stably recover without substantial changes in shape, even if various mechanical deformations occur in environments of room temperature or low temperature.
[0231] Figure 27 The graphs are used to measure the ion transport rates of the solid electrolytes in Experimental Examples 1-4 of this application.
[0232] Reference Figure 27 Calculate the relevant K values for the solid electrolytes prepared according to Experimental Examples 1-4 above. + Zn 2+ OH - TFSI - [Ch] + Ion transport rate of ions. For example... Figure 27 As shown, it was confirmed that the OH group... -Ions have the highest transport rate, OH - After ions, K + Ions have a high transport rate.
[0233] The specific ionic conductivity is shown in Table 2 below.
[0234] Table 2
[0235]
[0236] Preparation of solid electrolytes in Experiments 2-1 to 2-5
[0237] Solid electrolytes were prepared using the same method as in Experimental Examples 1-4 above. The proportions of the first composite fiber (oCBC) in Experimental Example 1-2 and the second composite fiber (qCBC) in Experimental Example 1-3 were adjusted according to the proportions shown in Table 3 below to prepare the solid electrolytes of Experimental Examples 2-1 to 2-5.
[0238] Table 3
[0239] Experimental Example 2-1 10% by weight 90% by weight Experimental Example 2-2 30% by weight 70% by weight Experimental Example 2-3 50% by weight 50% by weight Experimental Example 2-4 70% by weight 30% by weight Experimental Example 2-5 90% by weight 10% by weight
[0240] Figure 28 The results are X-ray diffraction analysis results of the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0241] Reference Figure 28 X-ray diffraction analysis was performed on the solid electrolytes of Experimental Examples 2-1 to 2-5 above.
[0242] exist Figure 28 As can be seen from the results, the solid electrolytes of Experimental Examples 2-1 to 2-5 have peak values corresponding to the (101) and (002) crystal planes. The crystal structure does not change substantially with the ratio of the first composite fiber (oCBC) and the second composite fiber (qCBC). However, with the increase of the ratio of the second composite fiber, the 2θ value of the peak value corresponding to the (002) crystal plane increases slightly.
[0243] Figure 29 The Fourier transform infrared spectroscopy analysis results are for the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0244] Reference Figure 29 Fourier transform infrared spectroscopy analysis was performed on the solid electrolytes of Experimental Examples 2-1 to 2-5 above.
[0245] exist Figure 29 In the middle, at 2916cm -1 and 3320cm -1The vibrations in the solid electrolytes prepared according to Experimental Example 2-3, which have the same ratio of first composite fiber to second composite fiber, correspond to the OH stretching vibrations. It can be confirmed that the intensity of the OH stretching vibrations of the solid electrolytes prepared according to Experimental Example 2-3 is significantly higher than that of the solid electrolytes prepared according to Experimental Example 2-1, Experimental Example 2-2, Experimental Example 2-4 and Experimental Example 2-5.
[0246] In other words, controlling the proportion of the first composite fiber to be greater than 30% by weight and less than 70% by weight, and controlling the proportion of the second composite fiber to be less than 70% by weight and greater than 30% by weight, is an effective method to increase the content of OH ions in the solid electrolyte, thereby resulting in an increase in the ionic conductivity of OH ions.
[0247] Figure 30 The results were obtained to measure the ion transport rate of the solid electrolytes in Experimental Examples 2-1 to 2-55 of this application based on temperature.
[0248] Reference Figure 30 The ionic conductivity of the solid electrolytes in Experiments 2-1 to 2-5 was measured at temperature, and the ionic conductivity of commercially available A201 membranes was measured at temperature for comparison.
[0249] exist Figure 30 As can be seen, the ionic conductivity of the solid electrolyte and the A201 membrane in Experiments 2-1 to 2-5 increases with increasing temperature. Furthermore, it can be confirmed that the ionic conductivity of the solid electrolyte in Experiments 2-1 to 2-5 is significantly higher than that of the A201 membrane.
[0250] Based on this, it can be confirmed that the solid electrolyte prepared according to Example 2-3 with the same ratio of first composite fiber to second composite fiber has a significantly higher ionic conductivity than the solid electrolytes of Examples 2-1, 2-2, 2-4, and 2-5. As a result, it can be confirmed that controlling the proportion of the first composite fiber to be greater than 30% by weight and less than 70% by weight, and controlling the proportion of the second composite fiber to be less than 70% by weight and greater than 30% by weight, is an effective method to improve the ionic conductivity of OH ions.
[0251] Figure 31 The graphs were used to measure the water immersion rate and expansion ratio of the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0252] Reference Figure 31 The water immersion rate and expansion ratio of the solid electrolytes in Experiments 2-1 to 2-5 were measured according to temperature, and the water immersion rate and expansion ratio of commercially available A201 membranes were measured according to temperature for comparison.
[0253] exist Figure 31 As can be seen, the water immersion rate of the solid electrolyte and the A201 membrane in Experiments 2-1 to 2-5 increases with increasing temperature. Furthermore, it can be confirmed that the water immersion rate of the solid electrolyte in Experiments 2-1 to 2-5 is significantly higher than that of the A201 membrane.
[0254] Based on this, it can be confirmed that the water immersion rate of the solid electrolyte prepared according to Experimental Example 2-3 with the same ratio of first composite fiber to second composite fiber is significantly higher than that of the solid electrolytes in Experimental Example 2-1, Experimental Example 2-2, Experimental Example 2-4 and Experimental Example 2-5.
[0255] Furthermore, it can be confirmed that the expansion ratio of the A201 membrane increases significantly with increasing temperature. Conversely, it can be confirmed that the expansion ratio of the solid electrolytes in Experiments 2-1 to 2-5 is significantly low with increasing temperature, and the expansion ratio of the solid electrolyte in Experiment 2-3 does not change substantially even with increasing temperature.
[0256] As a result, it can be seen that controlling the proportion of the first composite fiber to be greater than 30% by weight and less than 70% by weight, and controlling the proportion of the second composite fiber to be less than 70% by weight and greater than 30% by weight, is an effective method to improve the water immersion rate and minimize the expansion ratio with temperature and the change in the expansion ratio.
[0257] Figure 32 Arrhenius plots of the conductivity of the solid electrolytes in Experimental Examples 2-1 to 2-5 of this application.
[0258] Reference Figure 32 The diagram shows the Arrhenius plots of the solid electrolyte and A201 membrane for Experimental Examples 2-1 to 2-5 above.
[0259] exist Figure 32 As can be seen, the conductivity of the solid electrolytes in Experiments 2-1 to 2-5 increases with increasing temperature. Furthermore, the conductivity of the solid electrolytes in Experiments 2-1 to 2-5 is significantly higher than that of the A201 film.
[0260] Based on this, it can be confirmed that the conductivity of the solid electrolyte prepared according to Experimental Example 2-3 with the same ratio of first composite fiber to second composite fiber is significantly higher than that of the solid electrolytes in Experimental Example 2-1, Experimental Example 2-2, Experimental Example 2-4 and Experimental Example 2-5.
[0261] As a result, it can be seen that controlling the proportion of the first composite fiber to be greater than 30% by weight and less than 70% by weight, and controlling the proportion of the second composite fiber to be less than 70% by weight and greater than 30% by weight, is an effective method to improve conductivity.
[0262] Preparation of solid electrolytes in Experiments 3-1 to 3-5
[0263] Based on the above experimental examples, basic composite fibers were prepared, and the proportion of chitosan derivatives added was adjusted to prepare basic composite fibers with different chitosan contents. Then, based on the above experimental examples 1-4, solid electrolytes were prepared using basic composite fibers with different chitosan contents.
[0264] Prepare chitosan for Experiments 3-6
[0265] Pure chitosan was prepared as a comparative example for Experiments 3-1 to 3-5 above.
[0266] The chitosan content in the solid electrolytes of Experiments 3-1 to 3-6 is shown in Table 4 below.
[0267] Table 4
[0268] Experimental Example 3-1 10% by weight Experimental Example 3-2 30% by weight Experimental Example 3-3 50% by weight Experimental Example 3-4 70% by weight Experimental Example 3-5 90% by weight Experimental Example 3-6 100% by weight
[0269] Figures 33 to 35 The results of X-ray photoelectron spectroscopy analysis of the solid electrolytes in Experiments 3-1 to 3-5 and the bacterial cellulose in Experiments 1-5 of this application are as follows: Figure 36 To analyze the elemental ratio curves of the solid electrolytes in Experiments 3-1 to 3-5 and the bacterial cellulose in Experiments 1-5 of this application, Figure 37 To analyze the composition ratio of the C1s spectra of the solid electrolytes in Experimental Examples 3-1 to 3-5 and the bacterial cellulose in Experimental Examples 1-5 of this application, Figure 38 The results were used to analyze the composition ratio of the N1s spectra of the solid electrolytes in Experimental Examples 3-1 to 3-5 and the bacterial cellulose in Experimental Examples 1-5 of this application.
[0270] Reference Figures 33 to 38 X-ray photoelectron spectroscopy analysis was performed on the solid electrolytes of Experiments 3-1 to 3-5 and the bacterial cellulose of Experiments 1-5 (omitting chitosan). Figure 36 As shown, the elemental ratios within the solid electrolyte are analyzed, such as... Figure 37 As shown, the composition ratio of the C1s spectrum is analyzed, as follows: Figure 38 As shown, the composition ratio of the N1s spectrum is analyzed. Figure 33 The spectrum is C1s. Figure 34 For O1s spectrum, Figure 35 This is the N1s spectrum.
[0271] In the case of solid electrolytes in Experiments 3-1 to 3-5, compared with bacterial cellulose in Experiments 1-5 where chitosan was omitted, CN bonds were observed as chitosan and bacterial cellulose were combined.
[0272] Furthermore, in Figure 33 and Figure 37 It can be seen that as the proportion of chitosan increases from 0% to 50% by weight, the proportion of CN also increases, while as the proportion of chitosan increases from 50% to 90% by weight, the proportion of CN decreases. In other words, it can be confirmed that when the proportion of chitosan is greater than 30% by weight and less than 70% by weight, the proportion of CN in the solid electrolyte is significantly high.
[0273] Furthermore, in Figure 35 and Figure 38 It can be confirmed that no nitrogen peak was detected in the bacterial cellulose of Examples 1-5, which omitted chitosan. While the proportion of nitrogen oxides generally increased with increasing chitosan content, the proportion of pyrrolic nitrogen (N) increased from 0% to 50% by weight of chitosan, and decreased from 50% to 90% by weight. In other words, it can be confirmed that when the chitosan content is greater than 30% to less than 70% by weight, the pyrrolic nitrogen content in the solid electrolyte is significantly high.
[0274] Furthermore, in Figure 36 As can be seen, the higher the proportion of chitosan, the higher the proportion of nitrogen. In Experiments 3-5, where the chitosan proportion was greater than 90% by weight, a nitrogen proportion of 6.63% by weight was confirmed.
[0275] Figure 39 The results are X-ray diffraction analysis of the solid electrolytes in Experimental Examples 3-1 to 3-5, the chitosan in Experimental Example 3-6, and the bacterial cellulose in Experimental Examples 1-5 of this application.
[0276] Reference Figure 39 X-ray diffraction analysis was performed on the solid electrolytes of Experiments 3-1 to 3-5, the chitosan of Experiment 3-6, and the bacterial cellulose of Experiments 1-5 (excluding chitosan).
[0277] exist Figure 39 As can be seen from the results, the chitosan in Experiments 3-6 does not exhibit any specific peaks. Compared with the bacterial cellulose in Experiments 1-5, the solid electrolytes in Experiments 3-1 to 3-6 have lower crystallinity.
[0278] Furthermore, it can be confirmed that as the proportion of chitosan gradually increases, the crystallinity gradually decreases and it becomes an amorphous phase, similar to chitosan. In particular, it can be confirmed that when the proportion of chitosan in Experimental Examples 3-4 is 70% by weight or more, the crystallinity decreases sharply.
[0279] Figure 40The results of measuring the ionic conductivity at temperature of the solid electrolytes in Experimental Examples 3-1 to 3-5, the chitosan in Experimental Example 3-6, the bacterial cellulose in Experimental Examples 1-5, and the ordinary bacterial cellulose in Experimental Examples 1-6 of this application are presented.
[0280] Reference Figure 40 The ionic conductivity of solid electrolytes in Experiments 3-1 to 3-5, chitosan in Experiment 3-6, bacterial cellulose with chitosan omitted in Experiments 1-5, and ordinary bacterial cellulose in Experiments 1-6 was measured based on temperature.
[0281] exist Figure 40 As can be seen, the higher the temperature, the greater the ionic conductivity of the solid electrolytes in Examples 3-1 to 3-5, the chitosan in Example 3-6, the bacterial cellulose without chitosan in Examples 1-5, and the ordinary bacterial cellulose in Examples 1-6. Furthermore, compared to the ordinary bacterial cellulose in Examples 1-6 and the chitosan in Examples 3-6, it can be confirmed that the bacterial cellulose in Examples 1-5 of the present invention has a higher ionic conductivity, and the ionic conductivity of the solid electrolytes in Examples 3-1 to 3-5 is significantly higher than that of the bacterial cellulose without chitosan in Examples 1-5, the ordinary bacterial cellulose in Examples 1-6, and the chitosan in Examples 3-6.
[0282] Based on this, it can be confirmed that the ionic conductivity of the solid electrolyte with 50% chitosan in Experimental Example 3-3 is significantly higher than that of the solid electrolytes in Experimental Examples 3-1, 3-2, 3-4, and 3-5. As a result, it can be confirmed that controlling the proportion of chitosan in the solid electrolyte to less than 30% and greater than 70% by weight is an effective method to improve the ionic conductivity of OH ions.
[0283] Figure 41 The results were obtained by measuring the expansion ratio of solid electrolytes in Experimental Examples 3-1 to 3-5, chitosan in Experimental Example 3-6, bacterial cellulose in Experimental Examples 1-5, and ordinary bacterial cellulose in Experimental Examples 1-6 according to temperature.
[0284] Reference Figure 41 The swelling ratios of the solid electrolytes in Experiments 3-1 to 3-5, the chitosan in Experiment 3-6, the bacterial cellulose in Experiments 1-5, and the ordinary bacterial cellulose in Experiments 1-6 were measured based on temperature.
[0285] exist Figure 41As can be seen, the expansion ratio of the solid electrolytes in Experiments 3-1 to 3-5, the chitosan in Experiment 3-6, the bacterial cellulose (omitting chitosan) in Experiments 1-5, and the ordinary bacterial cellulose in Experiments 1-6 increases with increasing temperature. Furthermore, it can be confirmed that the expansion ratio of the bacterial cellulose in Experiments 1-5 is not only lower than that of the ordinary bacterial cellulose in Experiments 1-6 and the chitosan in Experiments 3-6, but also lower than that of Experiments 3-1, 3-2, 3-4, and 3-5.
[0286] Based on this, it can be confirmed that the swelling ratio of the solid electrolyte with 50% chitosan in Experimental Example 3-3 is not only lower than that of the solid electrolytes in Experimental Examples 3-1, 3-2, 3-4, and 3-5, but also significantly lower than that of the bacterial cellulose in Experimental Examples 1-5 of this application. As a result, it can be confirmed that controlling the proportion of chitosan in the solid electrolyte to be greater than 30% and less than 70% by weight is an effective method to reduce the swelling ratio.
[0287] Figure 42 The results were obtained by measuring the water immersion rate of the solid electrolytes in Experimental Examples 3-1 to 3-5, the chitosan in Experimental Example 3-6, the bacterial cellulose in Experimental Examples 1-5, and the ordinary bacterial cellulose in Experimental Examples 1-6.
[0288] Reference Figure 42 The water immersion rates of the solid electrolytes in Experiments 3-1 to 3-5, the chitosan in Experiment 3-6, the bacterial cellulose in Experiments 1-5, and the ordinary bacterial cellulose in Experiments 1-6 were measured based on temperature.
[0289] exist Figure 42 As can be seen, the higher the temperature, the higher the water immersion rate of the solid electrolytes in Experiments 3-1 to 3-5, the chitosan in Experiment 3-6, the bacterial cellulose without chitosan in Experiment 1-5, and the ordinary bacterial cellulose in Experiment 1-6.
[0290] Within the normal temperature range, it was confirmed that the water immersion rate of the solid electrolyte containing 50% chitosan in Experimental Example 3-3 was not only higher than that of the solid electrolytes in Experimental Examples 3-1, 3-2, 3-4, and 3-5, but also higher than that of bacterial cellulose (omitting chitosan) in Experimental Examples 1-5, ordinary bacterial cellulose in Experimental Examples 1-6, and chitosan in Experimental Example 3-6. As a result, it was confirmed that controlling the proportion of chitosan in the solid electrolyte to be greater than 30% and less than 70% by weight is an effective method to improve the water immersion rate.
[0291] Figure 43This is a graph illustrating the results of measuring the voltage of the solid electrolyte in Experimental Examples 1-4 of this application.
[0292] Reference Figure 43 The solid electrolytes from Experiments 1-4 above were inserted between the zinc electrodes, and the temperature was 5 mA / cm. -2 10mAcm -2 and 20mAcm -2 Voltage was measured under the current density conditions. Under the same conditions, an A201 membrane was used instead of the solid electrolyte in Experiments 1-4 to be inserted between the zinc electrodes to measure the voltage. Figure 43 The graph at the top shows the voltage values in 999 and 1000 consecutive cycles. Figure 43 The image at the bottom is a scanning electron microscope image of the zinc electrode after 1000 scans.
[0293] exist Figure 43 As can be seen from the above, when using the A201 membrane, it stops working after about 23 hours, but when using the solid electrolyte of Experimental Examples 1-4 of this application, it can be confirmed that it works stably at high current density until the 1000th time.
[0294] Furthermore, in Figure 43 The scanning electron microscope image below confirms that even with prolonged application of high-density current, no dendrites are generated, and the device functions stably.
[0295] Figure 44 This is a graph illustrating the charge-discharge capacity of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application.
[0296] Reference Figure 44 Metal-air batteries were prepared using the solid electrolyte, copper, phosphorus, and sulfur compound constructs as positive electrodes, and cast zinc negative electrodes as described in Examples 1-4 above. Under the same conditions, commercially available Pt / C and RuO2 were used to replace the copper, phosphorus, and sulfur compound constructs as positive electrodes to prepare metal-air batteries (Pt / C).
[0297] The positive electrode is prepared by a compound structure of copper, phosphorus and sulfur using the following method.
[0298] Prepare three ethanol / ethylenediamine suspensions, add dithiooxamide, tetradecylphosphonic acid / ifosfamide, and copper chloride respectively, and then stir.
[0299] Next, dithiocarbamate and tetradecylphosphonic acid / isocyclophosphamide were added to the copper chloride solution gradually and continuously while stirring. Then, ammonium hydroxide was added while stirring for 2 hours.
[0300] The resulting black suspension of copper-dithiooxamide-tetradecylphosphonic acid-ifosfamide was convected at 120°C for 6 hours, collected by centrifugation, washed with deionized water and ethanol, and then dried in vacuum.
[0301] The obtained copper-dithiocarbamate-tetradecylphosphonic acid-isocyclophosphamide precursor suspension was then mixed with deionized water and sodium bisulfite containing Triton X-165 in an ice bath. The reaction suspension was then subjected to pressure heat treatment (autoclave) followed by cooling to room temperature. The resulting black solid sponge was washed with deionized water and ethanol until the supernatant reached a neutral pH.
[0302] The generated product was immersed in liquid nitrogen at -70°C and freeze-dried under vacuum for 2 hours to prepare a copper, phosphorus, and sulfur compound-structured cathode material. A slurry was prepared by mixing the cathode material (90% by weight), super P carbon black (5% by weight), and polytetrafluoroethylene (PTFE) (5% by weight) into an N-methyl-pyrrolidone solution containing 0.5% by weight of perfluorosulfonic acid (Nafion). The slurry was coated onto a stainless steel mesh to evaporate the solvent. Then, it was cut into 6cm × 1.5cm pieces and dried to prepare the cathode.
[0303] exist Figure 44 From this, it can be confirmed that at 25mAcm -2 and 50mAcm -2 Under certain conditions, it exhibits excellent charge and discharge capacity. When using the copper, phosphorus, and sulfur compound constructs prepared as described above, it can be confirmed that it has a significantly higher capacity compared to the case using Pt / C and RuO2.
[0304] Figure 45 The voltage values of metal-air batteries containing solid electrolytes from Experimental Examples 1-4 of this application are measured based on the number of charge-discharge cycles.
[0305] Reference Figure 45 At 50mAcm -2 Conditions and 25mA -2 Under these conditions, the reference is determined based on the number of charge-discharge cycles. Figure 44 The voltage values of the metal-air battery using the solid electrolyte, copper, phosphorus and sulfur compound constructs of the positive electrode and the cast zinc negative electrode of the above experimental examples 1-4 are explained.
[0306] exist Figure 45 As can be seen, stable operation can be confirmed during approximately 600 charge-discharge cycles. That is, it can be confirmed that the solid electrolyte prepared according to the embodiments of the present invention described above can be stably used as a solid electrolyte for metal-air batteries.
[0307] Figure 46 This is a graph illustrating the changes in charge-discharge characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application under external temperature conditions.
[0308] Reference Figure 46 The reference was tested when the external temperature changed from -20℃ to 80℃. Figure 44 This describes the changes in charge-discharge characteristics of metal-air batteries using solid electrolytes (CBCs), copper, phosphorus, and sulfur compounds as positive electrodes, and cast zinc negative electrodes as described in Experiments 1-4 above. Figure 46 Part (b) is at a current density of 25 mA / cm². -2 The results of the test under the circumstances.
[0309] exist Figure 46 As can be seen, the voltage increases with increasing temperature, exhibiting a low overpotential. That is, it can be confirmed that the secondary battery containing the solid electrolyte of Experimental Examples 1-4 of this application can be stably operated in both high and low temperature environments.
[0310] Figure 47 The graph illustrates the retention characteristics of metal-air batteries containing the solid electrolytes of Experimental Examples 1-4 of this application in low-temperature and high-temperature environments based on the number of charge-discharge cycles.
[0311] Reference Figure 47 With the external temperature controlled at -20℃ and 80℃, at 25mAcm -2 Under the condition of reference Figure 44 The metal-air battery described above utilizes solid electrolytes (CBCs), copper, phosphorus, and sulfur compound constructs as positive electrodes, and a cast zinc negative electrode to perform charge-discharge cycles.
[0312] exist Figure 44 It can be seen that the retention characteristics decreased slightly under the condition of -20℃, but it can be confirmed that after 1500 charge-discharge cycles at high and low temperatures, it still maintains a high retention characteristic of about 94.5% and drives stably.
[0313] Figure 48A graph illustrating the charge-discharge characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application, based on external temperature.
[0314] Reference Figure 48 With the external temperature controlled at -20℃, 25℃, and 80℃, at 25mAcm -2 Measurement reference under the conditions Figure 44 The charge and discharge voltages of the metal-air battery using the solid electrolytes (CBCs), copper, phosphorus, and sulfur compounds of Experiment Examples 1-4 above, and the cast zinc anode are shown, along with Nyquist plots.
[0315] exist Figure 48 As can be seen, only a slight decrease in properties was observed in low-temperature environments, but it can be confirmed that it works stably at low, normal, and high temperatures.
[0316] Figure 49 A graph illustrating the capacity characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application as a function of external temperature.
[0317] Reference Figure 49 With the external temperature controlled between -40℃ and 105℃, at 25mAcm -2 The capacity of metal-air batteries using solid electrolytes (CBCs), copper, phosphorus and sulfur compound constructs as positive electrodes and cast zinc negative electrodes from Experiment Examples 1-4 were measured under the above conditions.
[0318] exist Figure 49 As can be seen, a high capacity of over 1 Ah can be confirmed within the temperature range of -20℃ to 80℃. Conversely, at temperatures below -20℃, the mobility of OH ions within the solid electrolyte decreases sharply, leading to a sharp decrease in capacity. At temperatures above 80℃, the capacity characteristics deteriorate sharply due to the evaporation of the solvent within the solid electrolyte. Specifically, the capacity decreases significantly to 0.234 Ah at -40℃ and to 0.394 Ah at 105℃.
[0319] Figure 50 This is a graph illustrating the charge-discharge characteristics of a metal-air battery containing the solid electrolytes of Experimental Examples 1-4 of this application under charge-discharge cycles at external temperature.
[0320] Reference Figure 50 With the external temperature controlled at -20℃ and 80℃, at 25mAcm -2 Under the conditions of using the reference within 200 hours Figure 44The metal-air batteries described in Experiments 1-4 above, consisting of solid electrolytes (CBCs), copper, phosphorus, and sulfur compound constructs as positive electrodes, and cast zinc negative electrodes, were charged and discharged 1500 times. Figure 50 Part (a) shows the results of charging and discharging under conditions of -20°C. Figure 50 Part (b) shows the results of charging and discharging at 80°C.
[0321] exist Figure 50 As can be seen, although the charge and discharge characteristics decrease slightly in a low-temperature environment of -20℃, the system can still drive stably for a long time, and it can also drive stably for a long time in a high-temperature environment of 80℃.
[0322] Figure 51 A block diagram illustrating an embodiment of the electric vehicle of the present invention.
[0323] Reference Figure 51 The electric vehicle 1000 of the present invention may include at least one of the following: motor 1010, transmission 1020, axle 1030, battery pack 1040, power control unit 1050 and charging unit 1060.
[0324] The aforementioned motor 1010 can convert the electrical energy of the aforementioned battery pack 1040 into kinetic energy. The kinetic energy converted by the aforementioned electrode 1010 can be provided to the aforementioned axle 1030 through the aforementioned transmission 1020. The aforementioned motor 1010 can be composed of a single motor or multiple electrodes. For example, when the aforementioned motor 1010 is composed of multiple electrodes, the aforementioned motor 1010 may include a front wheel motor that provides kinetic energy to the front wheel axle and a rear wheel motor that provides kinetic energy to the rear wheel axle.
[0325] The aforementioned transmission 1020 is located between the aforementioned motor 1010 and the aforementioned axle 1030, and can provide the kinetic energy generated by the aforementioned motor 1010 to the aforementioned axle 1030 in a manner that conforms to the driving environment desired by the driver.
[0326] The battery pack 1040 can store electrical energy through the charging unit 1060 and supply the stored electrical energy to the motor 1010. The battery pack 1040 can supply electrical energy directly to the motor 1010 or supply electrical energy through the power control unit 1050.
[0327] In this case, the battery pack 1040 described above may consist of at least one battery cell. Furthermore, the battery cell may include a metal-air secondary battery containing the solid electrolyte of the embodiments of the present invention described above, but is not limited thereto; it may also include secondary batteries of various types. On the other hand, a battery cell may be a term referring to individual batteries, while a battery pack may refer to an assembly of battery cells interconnected, having a desired voltage and / or capacity.
[0328] The aforementioned power control unit 1050 can control the aforementioned battery pack 1040. That is, the power control unit 1050 can control the power supplied from the battery pack 1040 to the motor 1010 to have the required voltage, current, waveform, etc. For this purpose, the power control unit 1050 may include at least one of passive power devices and active power devices.
[0329] The aforementioned charging unit 1060 can be from Figure 43 The external power source 1070 shown receives power to supply the battery pack 1040. The charging unit 1060 can control the charging state as a whole. For example, the charging unit 1060 can control the on / off state of charging and the charging speed.
[0330] The present invention has been described in detail above using preferred embodiments, but the scope of the invention is not limited to the specific embodiments, but should be interpreted through the appended claims. Furthermore, it should be understood that those skilled in the art can make various modifications and variations without departing from the scope of the invention.
[0331] Industrial applicability
[0332] The solid electrolyte of this application embodiment can be used in various industrial fields such as secondary batteries, energy storage units, electric vehicle batteries, water electrolysis batteries and fuel cells.
Claims
1. A solid electrolyte, characterized in that, It comprises a basic composite fiber containing bacterial cellulose and chitosan bound to the aforementioned bacterial cellulose. The surface of the bacterial cellulose containing the chitosan is bound to a nitrogen-containing first functional group, wherein the solid electrolyte comprises: The surface of the aforementioned basic composite fiber is oxidized to that of the first composite fiber; and The second composite fiber, on the surface of the aforementioned basic composite fiber, is bonded to the first functional group. The proportion of the first composite fiber is greater than 30% by weight and less than 70% by weight. The proportion of the second composite fiber mentioned above is less than 70% by weight and greater than 30% by weight. The first functional group is represented by the following chemical formula 1, and is linked to the bacterial cellulose containing the chitosan via one of the two nitrogen atoms of the first functional group: Chemical Formula 1: 。 2. The solid electrolyte according to claim 1, characterized in that, The aforementioned basic composite fibers contain a mixture of crystalline and amorphous phases.
3. The solid electrolyte according to claim 1, characterized in that, The surface of the bacterial cellulose containing the chitosan was oxidized.
4. The solid electrolyte according to claim 3, characterized in that, The surface of the bacterial cellulose bound with the above-mentioned chitosan was oxidized using an aqueous solution of 2,2,6,6-tetramethylpiperidine-1-oxy.
5. The solid electrolyte according to claim 1, characterized in that, The aforementioned second composite fiber comprises a brominated base composite fiber.
6. The solid electrolyte according to claim 5, characterized in that, The first composite fiber and the second composite fiber are cross-linked together.
7. A solid electrolyte, characterized in that, Include: Membranes containing cellulose; and Chitosan, bound to the cellulose in the above-mentioned membrane, in an amount greater than 30% by weight and less than 70% by weight. Among them, the solid electrolyte exhibits the highest ionic conductivity when the chitosan content is greater than 30% by weight and less than 70% by weight. In this process, the surface of the cellulose containing the chitosan is bonded to a first functional group having nitrogen. The aforementioned solid electrolyte comprises: The surface of the basic composite fiber is oxidized in the first composite fiber; and The second composite fiber, on the surface of the aforementioned basic composite fiber, is bonded to the first functional group. The proportion of the first composite fiber is greater than 30% by weight and less than 70% by weight. The proportion of the second composite fiber mentioned above is less than 70% by weight and greater than 30% by weight. The first functional group is represented by the following chemical formula 1, and is linked to the cellulose containing the chitosan via one of the two nitrogen atoms of the first functional group: Chemical Formula 1: 。 8. The solid electrolyte according to claim 7, characterized in that, With chitosan at a weight percentage of 50%, X-ray photoelectron spectroscopy analysis showed that the proportion of CN bonds had a maximum value in the C1s spectrum.
9. The solid electrolyte according to claim 7, characterized in that, The cellulose mentioned above includes bacterial cellulose.
10. A solid electrolyte, characterized in that, Include: Membranes containing cellulose; and Chitosan, bound to the cellulose in the above-mentioned membrane, in an amount greater than 30% by weight and less than 70% by weight. Specifically, when the chitosan content is greater than 30% by weight and less than 70% by weight, the solid electrolyte exhibits the lowest swelling ratio. In this process, the surface of the cellulose containing the chitosan is bonded to a first functional group having nitrogen. The aforementioned solid electrolyte comprises: The first composite fiber, with the surface of the cellulose bound to the chitosan described above oxidized; and The second composite fiber, which combines with the surface of the cellulose bound to the chitosan, and with the first functional group, The proportion of the first composite fiber is greater than 30% by weight and less than 70% by weight. The proportion of the second composite fiber mentioned above is less than 70% by weight and greater than 30% by weight. The first functional group is represented by the following chemical formula 1, and is linked to the cellulose containing the chitosan via one of the two nitrogen atoms of the first functional group: Chemical Formula 1: 。 11. The solid electrolyte according to claim 10, characterized in that, As the proportion of chitosan increases, the crystallinity gradually decreases.
12. A method for preparing a solid electrolyte, characterized in that, include: Steps for preparing chitosan derivatives; The steps for generating chitosan bound to cellulose from the above-mentioned chitosan derivatives; The step of preparing the first composite fiber by oxidizing the surface of the cellulose with the chitosan attached thereto using an oxidizing agent; The step of preparing a second composite fiber by binding bromine to the surface of the cellulose containing the chitosan described above, and then replacing the bromine with a first functional group containing nitrogen. The step of crosslinking the first composite fiber and the second composite fiber; and The steps for preparing a solid electrolyte using the cross-linked first composite fiber and the second composite fiber described above. In this process, the surface of the cellulose containing the chitosan is bonded to a first functional group having nitrogen. The first functional group is represented by the following chemical formula 1, and is linked to the cellulose containing the chitosan via one of the two nitrogen atoms of the first functional group: Chemical Formula 1: 。 13. The method for preparing a solid electrolyte according to claim 12, characterized in that, Crystallinity, ionic conductivity, and expansion ratio are controlled based on the proportions of the chitosan derivatives mentioned above.
14. The method for preparing a solid electrolyte according to claim 12, characterized in that, The cellulose mentioned above includes bacterial cellulose.
15. The method for preparing a solid electrolyte according to claim 14, characterized in that, The steps for generating the chitosan bound to the cellulose described above include: The steps for preparing a culture medium containing the above-mentioned chitosan derivatives; and The steps of injecting bacterial strains into the above culture medium and culturing them.
Citation Information
Patent Citations
Electrolyte-electrode assembly, method for manufacturing same, and electrochemical device comprising same
WO2014200198A1
Preparation method of full-interpenetrating-type quaternized chitosan anion exchange membrane
CN105733004A
Method for preparing cross-linked QCS-CM-Guanidine full-interpenetrating anion-exchange membrane
CN106784949A